18S Ribosomal RNA Evaluation as Preanalytical Quality Control for Animal DNA. (8th September 2016) - Leonard, Cory Ann; Meli, Marina L.; Novacco, Marilisa; Borel, Nicole
Abstract : The 18S ribosomal RNA (rRNA) gene is present in all eukaryotic cells. In this study, we evaluated the use of this gene to verify the presence of PCR-amplifiable host (animal) DNA as an indicator of sufficient sample quality for quantitative real-time PCR (qPCR) analysis. We compared (i) samples from various animal species, tissues, and sample types, including swabs; (ii) multiple DNA extraction methods; and (iii) both fresh and formalin-fixed paraffin-embedded (FFPE) samples. Results showed that 18S ribosomal RNA gene amplification was possible from all tissue samples evaluated, including avian, reptile, and FFPE samples and most swab samples. A single swine rectal swab, which showed sufficient DNA quantity and the demonstrated lack of PCR inhibitors, nonetheless was negative by 18S qPCR. Such a sample specifically illustrates the improvement of determination of sample integrity afforded by inclusion of 18S rRNA gene qPCR analysis in addition to spectrophotometric analysis and the use of internal controls for PCR inhibition. Other possible applications for the described 18S rRNA qPCR are preselection of optimal tissue specimens for studies or preliminary screening of archived samples prior to acceptance for biobanking projects.